Boosting innovation and growth through the use of design - Nevado, Pedro Picaluga; Barata, José Monteiro; Almendra, Rita Assoreira (Journal of Business Economics and Management, 2016)
The question underpinning this study is: would the incorporation of design throughout every dimension of a company's business pursuing innovation result in higher levels of growth and competitiveness? The paper begins with a brief theoretical approach to the concepts of creativity, design and innovation and identifies some of the traditional company growth strategies. This paper provides, in the context of design management, a first empirical analysis on the relationship between company growth and the investments in design along the value chain, stressing the importance of the phase in which design gets applied for the first time (“momentum”). The empirical analysis was based on data captured from an online questionnaire on the Portuguese manufacturing industry. The multivariate data analysis focused on the analysis of variance and factor analysis. The pa- per has the merit to conclude that the companies growing more sharply apply design from generating ideas to processes and production and extending into the marketing phase.